Pemberdayaan Masyarakat Dalam Implementasi Manajemen Berbasis Sekolah (MBS) Di SD Negeri 1 Menawan Grobogan - Bakdiyono, Bakdiyono, Prof. Dr. Bambang Sumardjoko (2017)
BAKDIYONO, NIM Q 100 150 005 Community Empowerment InMenejemen Implementation of School-Based Elementary School 1 Menawan Grobogan. Master's thesis Education Administration Studies Program Graduate School of Muhammadiyah University of Surakarta This study aims to, describing Preparation, Implementation and Evaluation of community empowerment in the implementation of school-based management in Elementary School country 1 Menawan subdistrict Klambu regency Grobogan. . type of Research diskriptif qualitative by desain is ethnography approach. technics of data collecting from document analysis, observation and interview the data Authenticity use four triangulation with the resource person headmaster, teacher and school committee. The results of the study, (1) Preparation of community development in the implementation of school-based management in elementary schoo country 1 Menawan, based on the results of research and discussion it can be concluded that, Preparation empowerment begins with the union or equate the perception and the purpose of each component of the perpetrator's empowerment including school committee through the application of MBS. Preparations continued by determining the location or feasibility studies. Continued or strung together with communication or socialization to related parties including stakeholders in the school headmaster here referring to the school-based management or MBS. (2) The implementation of community empowerment in the implementation of school-based management in Elementary Sechool country 1 Menawan, implementation of empowerment to do in general is to improve the capability and self-reliance in improving their living standards. Their implementation is, to assess the potential and the opportunities this event is intended to identify and analyze its cercumstance society, both the potential and problems. Apparently there are in implementation in concrete activities with regard to the realization and the initial plan. Is known also by monitoring the implementation of empowerment for the progress of development activities to the attention of all parties, but it also repairs if needed. (3) evaluation of community empowerment in the implementation of school management in Elementary School country 1 Menawan, control must be able to foster cooperation with parents and the community, create a conducive atmosphere and fun for students and school community in the implementation of the concept of MBS. Known also turned the school committee also had its share, especially in of that community empowerment is effective and not misplaced Keywords: MBS, empowerment, management